Asupan Energi, Zat Gizi Makro dan Pertambahan Berat Badan Ibu Hamil - Nurmela Setia Ningsih; Betty Yosephin Simanjuntak; Miratul Haya (Politeknik Kesehatan Tanjung Karang, 2021)
Pregnant women are one of the vulnerable groups. During pregnancy, there is an increase in the need for nutrients to meet the needs of the mother and fetus as well as preparation for labor. It is very important to pay attention to the recommended weight gain during pregnancy to prevent the occurrence of low birth weight. The purpose of this study was to determine the relationship between energy, carbohydrate, fat, and protein intake on weight gain of pregnant women in the city of Bengkulu. The design of this study was a cross-sectional study with a total sample of 47 pregnant women who had received an education of the first thousand days of life when registering to become a prospective bride at the Religious Affairs Office. As many as 53.2% of mothers had good weight gain and had a relationship between energy intake (p-value 0,032), carbohydrate intake (p-value 0,024), protein intake (p-value 0,039), and fat intake (p-value 0,023). Energy and macronutrients have a relationship with the weight gain of pregnant women in the group of preconception couples who have received education about the first 1000 days of life. It is hoped that pregnant women will be able to control their weight during pregnancy and apply the knowledge that has been obtained through education while preconception age.